PENGARUH JUMLAH WISATAWAN ASING, JUMLAH UANG BEREDAR DAN INFLASI TERHADAP NILAI TUKAR - Padmayoni, Ni Putu Krisnanda Sukma; Jember, I Made (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2020)
The exchange rate is a very important economic indicator because the movement of the exchange rate affects the economy of a country. In the floating exchange rate system, the exchange rate tends to fluctuate, it is caused by the movement of the exchange rate which is influenced by the strength of demand and supply in the foreign exchange market. This study to analyze the influence of the number of foreign tourists visiting Indonesia, the money supply and inflation rate on the rupiah exchange rate simultaneously and partially as well as analyzing the dominant variables that affect the rupiah exchange rate. The data used are secondary data (time series) quarterly for the period 2008-2017. The data analysis technique used is multiple linear regression analysis. The results of this study indicate that the number of foreign tourists, the money supply and the inflation rate simultaneously have a significant effect on the rupiah exchange rate, the number of foreign tourists, the money supply and the inflation rate partially have a positive and significant effect on the rupiah exchange rate, the dominant variable affecting the value rupiah exchange is the money supply. Keywords : Exchange rates, number of foreign tourist visits, money supply, inflation rates